PHRASEOLOGY IS A BRANCH OF GENERAL LINGUISTICS - Ibragimova Sojida Panjiyevna (Journals Park Publishing, 2022)
Two main families of phrasemes (= non-free phrases) are distinguish ed: lexical phrasemes and semantic-lexical phrasemes; the phrasemes of the first family are constrained only in their form (their meaning being free), those of the second family are constrained both in their meaning and in their form. Two basic concepts are introduced: compositionality of complex linguistic signs and the pivot of a meaning. Three major classes of phrasemes are presented: noncompositional idioms and compositional collocations and clichés. A new type of general dictionary is proposed, and the lexicographic presentation of the three classes of phrasemes is illustrated. To show how the proposed approach to phraseology can be used in Automatic Language Processing, three fully-fledged examples are examined in detail.
Keywords: phraseology; compositionality; pivot (of a meaning); idioms; collocations; clichés; lexicography; automatic language processing.